2019
DOI: 10.1002/jpen.1726
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Feeding Guidelines Improve Outcomes in Surgical Infants

Abstract: BackgroundEarly introduction of enteral nutrition (EN) in postoperative infants improves intestinal adaptation, reducing the risk of intestinal failure–associated liver disease (IFALD). Our objective was to determine whether guideline use reduces feeding variability and improves outcomes in the neonatal intensive care unit (NICU).MethodsIn a cohort study, surgical infants at risk for IFALD were evaluated pre and post implementation of feeding guidelines at 2 NICUs. A total of 167 guideline infants (2013–2018) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
2
7
0
1
Order By: Relevance
“…To the best of our knowledge there are few (if any) studies addressing the strategy of initiating ‘ oral or gavage feeding ’ fast track concepts in newborns with congenital duodenal disorders as to what may be best considered the ‘ideal method ‘of advancing postoperative feeding [ 7 ]. We show that the monitoring of gastric content was of itself less crucial for accelerating feeding [ 1 ] thus encouraging the working practice paradigm of ‘scaling up feeds’.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge there are few (if any) studies addressing the strategy of initiating ‘ oral or gavage feeding ’ fast track concepts in newborns with congenital duodenal disorders as to what may be best considered the ‘ideal method ‘of advancing postoperative feeding [ 7 ]. We show that the monitoring of gastric content was of itself less crucial for accelerating feeding [ 1 ] thus encouraging the working practice paradigm of ‘scaling up feeds’.…”
Section: Discussionmentioning
confidence: 99%
“…There may however be theoretical concerns whether perinatal or perioperative stressors could be risk factors for NEC. Rapid feeding or ‘fast track’ regimens could however return the neonate to a more physiologic homeostatic process [ 5 ] reducing risks of intestinal failure associated liver disease (IFALD) from prolonged parenteral alimentation [ 6 , 7 ], with a shortened hospital stay (LOS) and better long-term outcome. In the surgical practice of routine monitoring of newborn gastric residual volumes, some studies have suggested it does not have any clear advantage in accelerating feeding and / or monitoring or the early detection of NEC [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…In neonatal population, the rates are increased, particularly in patients with necrotizing enterocolitis (NEC). When PN is required for more than 60 days, IFALD occurs in more than 75% of cases ( 11 ). Although IFALD has a multifactorial origin, it is widely accepted that soy-based lipid emulsions (SO-LEs), used for parenteral nutrition, play a primary pathogenic role due to their high phytosterol content, high ω-6 to ω-3 long-chain polyunsaturated fatty acid ratio, and low levels of α - tocopherol ( 12 ).…”
Section: Prevalence Etiology and Risk Factorsmentioning
confidence: 99%
“…Their study showed that the implementation of guidelines focused on postoperative feeding has a favorable impact on many parameters such as the timing of onset of postoperative enteral feeding, the time to achieve enteral autonomy, the incidence rates of IFALD, the peak of direct bilirubin, the overall use of PN, and the length of hospitalization. Furthermore, faster feeding advancement is associated with significantly decreased IFALD severity, lower peak of direct bilirubin, and higher percentage of IFALD resolution by discharge ( 11 ). Breast milk and amino acid-based formula seem to be the best options to re-feed infants with IF.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…There may however be theoretical concerns whether perinatal or perioperative stressors could be risk factors for NEC. Rapid feeding or 'fast track' regimens could however return the neonate to a more physiologic homeostatic process [5] reducing risks of intestinal failure associated liver disease (IFALD) from prolonged parenteral alimentation [6,7], with a shortened hospital stay (LOS) and better long-term outcome. In the surgical practice of routine monitoring of newborn gastric residual volumes some studies have suggested it does not have any clear advantage in accelerating feeding and / or monitoring or the early detection of NEC [1].…”
Section: Introductionmentioning
confidence: 99%